2017
DOI: 10.1016/j.cgh.2016.09.096
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm to Predict Advanced Proximal Colorectal Neoplasia in Chinese Asymptomatic Population

Abstract: This study aims to develop and validate a new algorithm that incorporates distal colonoscopic findings to predict advanced proximal neoplasia (APN) in a Chinese asymptomatic population. We collected age, gender, and colonoscopic findings from a prospectively performed colonoscopy study between 2013 and 2015 in a large hospital-based endoscopy unit in Shanghai, China. Eligible subjects were allocated to a derivation group (n = 3,889) and validation group (n = 1,944) by random sampling. A new index for APN and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The newly developed risk prediction models between 2011 and 2021 predominantly originated from Asian countries (n = 19), including China [37,46,68,74], Korea [47,48,50,51,61,62,66,70,72], Japan [59,65], Thailand [57], Hong Kong [45,49], and Taiwan [56]. Among these novel risk prediction models based on Asian populations, the most common predictors were age (n = 19), smoking history (n = 17), sex (n = 15), BMI (n = 14), family history of CRC (n = 14), alcohol intake (n = 8), and diabetes mellitus (n = 6) [37,[45][46][47][48][49][50][51]56,57,59,61,62,65,66,68,70,72,74,80].…”
Section: Risk Predictors For Asian Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly developed risk prediction models between 2011 and 2021 predominantly originated from Asian countries (n = 19), including China [37,46,68,74], Korea [47,48,50,51,61,62,66,70,72], Japan [59,65], Thailand [57], Hong Kong [45,49], and Taiwan [56]. Among these novel risk prediction models based on Asian populations, the most common predictors were age (n = 19), smoking history (n = 17), sex (n = 15), BMI (n = 14), family history of CRC (n = 14), alcohol intake (n = 8), and diabetes mellitus (n = 6) [37,[45][46][47][48][49][50][51]56,57,59,61,62,65,66,68,70,72,74,80].…”
Section: Risk Predictors For Asian Populationsmentioning
confidence: 99%
“…All included studies, except for that of Jung et al (2018) and Briggs et al (2023), reported AUC values to assess the discriminatory accuracy of the models (Table 3). Among the 44 included models, 23 conventional risk models [37,40,42,[44][45][46][48][49][50][51]54,[58][59][60][61][63][64][65][67][68][69][70]72,74,75] and 10 composite models [39,41,47,56,57,62,71,75,76,80] reported AUC values with a 95% confidence interval (CI), as presented in Figure 5. Meanwhile, the model calibration was assessed in two different metrics: using the expected-to-observed (E/O) ratios, which were only demonstrated in nine of the studies; or by employing the Hosmer-Lemeshow (HL) goodness-of-fit test, as was the case in 12 out of 41 studies.…”
Section: Performance Of Risk Prediction Models For Crcmentioning
confidence: 99%
“…Subsequent validation in other populations might not result in similar discriminatory capabilities. 11 Third, there are concerns about the generalisability of these scores in people residing in different regions around the world. It is well recognised that the prevalence and distribution of advanced colorectal neoplasia differ for different ethnicities.…”
mentioning
confidence: 99%